Implementasi Sistem Pelaporan Kerusakan Lab Komputer Berbasis QR Code dengan Pendekatan Agile pada Mahasiswa - RM Chairil Andri; Risna Oktaviati (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
Computer lab facilities play a crucial role in supporting the learning process, particularly in the fields of engineering and technology. However, the manual reporting system for facility damages at the Computer Engineering Department, Politeknik Negeri Sriwijaya, is often inefficient and poorly documented. This study aims to analyze the impact of implementing a digital reporting system using QR Code technology on students' understanding and responsibility in maintaining lab facilities. The research employed the Agile Software Development method, encompassing five stages: requirements, design, development, testing, and deployment. Data were collected through interviews, literature reviews, as well as pre-test and post-test surveys using a Likert scale questionnaire. The results revealed a significant improvement in reporting experience (96.4%) and awareness of facility maintenance (92.8%) following the system's implementation. The system effectively facilitated real-time reporting of facility conditions by students and enhanced the efficiency of damage handling by technicians. Challenges, such as data input errors and QR Code sticker distribution, were addressed with corrective measures. This research contributes to the sustainable management of educational facilities and recommends further refinement to optimize the system.